Improving the Quality of Education Through Technology-Based Learning - Maryati, Sri; Susanto, Teguh Trianung Djoko; Mela, Angela Graciana Koli; Zebua, Joshua Obedience; Karomah, Fatihatul (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2024)
This study aims to determine the Improvement of Education Quality through Technology-Based Learning, The method used in this study is library research. Literature research is a research activity carried out by collecting data in the form of books, journals, and previous research results to support this research. The data collection method uses the help of the internet to browse various references to previous books and research journals that are in accordance with the topic of research discussion in the form of documentation from several books, theses, and online journals then processed and analyzed and conclusions are drawn. The results of this study explained that with the development of information technology can be utilized in the field of Education and will help teachers and students in carrying out the learning process. This research also contributes to providing examples of technology with various usability features in supporting the improvement of education quality, including by using Flipped classrooms, Learning Management Systems (LMS), Games (game-based learning) such as Duolingo applications, Augmented Reality (AR) and Virtual Reality (VR, and Khan Academy).